Characterizing cognitive aging of associative memory in animal models - Engle, James R.; Barnes, Carol A. (Frontiers in Aging Neuroscience, 2012)
An overview is provided of the simple single-cue delay and trace eyeblink conditioning paradigms as techniques to assess associative learning and memory in the aged. We highlight and focus this review on the optimization of the parameter space of eyeblink conditioning designs in the aged to avoid and control for potential confounds that may arise when studying aged mammals. The need to examine the contribution of non-associative factors that can contribute to performance outcomes is emphasized, and how age-related changes in the central nervous system as well as peripheral sensory factors can potentially bias the interpretation of the data in the aged is discussed. The way in which slight alterations of the parameter space in the delay and trace eyeblink conditioning paradigms can lead to delayed but intact conditioning, rather than impaired performance in aged animals is also discussed. Overall, the eyeblink conditioning paradigm, when optimized for the age of the animal in the study, is an elegantly simple technique for assessment of associative learning and memory. When design caveats described above are taken into account, this important type of memory, with its well-defined neural substrates, should definitely be included in cognitive assessment batteries for the aged.